Substituent effects on the solvent power of the haloolefin HCFO-1233 yd.(Z) - A. Fan; H. Zhou; D. Maksuta; R.J. Waltman (Results in Chemistry)
The solvent power of the hydrochlorofluoroolefin HCFO-1233 yd.(Z) is investigated using electron-withdrawing and electron-donating substituents on the “parent” (Z)-1-X-2,3,3-trifluoropropene, where X = NH2, OH, CH3O, CH3, F, H, Cl, COOH, CF3, CN, and NO2. The magnitude of the partial atomic charge on the 1‑hydrogen atom correlates to the Hammett σ+ substituent constant. The intermolecular interaction between CH3OH and the 1‑hydrogen atom is strengthened by electron-withdrawing 1-substituents producing smaller hydrogen bond distances and larger interaction energies. This work develops a Hammett-based structure-property correlation model to quantify electronic “push–pull” effects in HFO and HCFO solvent systems, guiding HCFO solvent design optimization to enhance its compatibility with PFPE lubricant polarity for hard disk drive application.